2017
DOI: 10.1073/pnas.1705601114
|View full text |Cite
|
Sign up to set email alerts
|

Haploid selection within a single ejaculate increases offspring fitness

Abstract: An inescapable consequence of sex in eukaryotes is the evolution of a biphasic life cycle with alternating diploid and haploid phases. The occurrence of selection during the haploid phase can have farreaching consequences for fundamental evolutionary processes including the rate of adaptation, the extent of inbreeding depression, and the load of deleterious mutations, as well as for applied research into fertilization technology. Although haploid selection is well established in plants, current dogma assumes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…Indeed, a recent study found evidence for haploid selection in zebrafish, presumably based on genetic differences among haploid gametes (Alavioon et al. ). The self‐incompatibility mechanisms in some plants and ascidians, which prevent self‐fertilization, also require expression of the haploid gamete allele (Takayama and Isogai ; Harada and Sawada ), indicating that such fine‐tuned mechanisms have evolved multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study found evidence for haploid selection in zebrafish, presumably based on genetic differences among haploid gametes (Alavioon et al. ). The self‐incompatibility mechanisms in some plants and ascidians, which prevent self‐fertilization, also require expression of the haploid gamete allele (Takayama and Isogai ; Harada and Sawada ), indicating that such fine‐tuned mechanisms have evolved multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we looked for a trade‐off between sperm swimming speed and sperm longevity, but did not find any (Alavioon et al. ). Whether a trade‐off may be found in any other aspect is currently unclear.…”
Section: Discussionmentioning
confidence: 84%
“…While increased sperm competition between different males can result in the evolution of trade-offs between sperm quantity and quality versus other traits, such as immune response (Simmons 2012), we currently have no evidence for any trade-off between selection for sperm longevity and offspring fitness with any other trait. In a previous study, we looked for a trade-off between sperm swimming speed and sperm longevity, but did not find any (Alavioon et al 2017). Whether a trade-off may be found in any other aspect is currently unclear.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studying these aspects of the phenotype will require improved methods to separate sperm with differing motility and probe their biochemistry and chromosomal content, with recent advances in microfluidics providing a potential route forward [47]. This work adds to the growing body of experimental and theoretical work demonstrating that even in animal sperm that undergo postmeiotic transcriptional shutdown, haploid selection within a single ejaculate is an important and underappreciated evolutionary force [49][50][51][52][53][54]. Our findings are supported by over two decades' worth of research by multiple groups that have demonstrated the evolutionary consequences of this sex ratio conflict for mouse genome structure and population genetics.…”
Section: Discussionmentioning
confidence: 99%